Finite-time control for an Unmanned Surface Vehicle based on adaptive sliding mode strategy. (15th June 2022) - Rodriguez, Jonathan; Castañeda, Herman; Gonzalez-Garcia, Alejandro; Gordillo, J.L.
Abstract: The proper control of the maximum convergence time toward a desired motion or trajectory is highly recommended for Unmanned Surface Vehicles (USV) in the case of autonomous trajectory tracking navigation and obstacle avoidance scenarios. This manuscript proposes to control the convergence time of an adaptive sliding mode controller applied to an autonomous vessel prototype subject to bounded perturbations. In the proposed approach, the maximum settling time is defined as a user input conditioning the controller design and tuning. To guarantee such convergence time to a small neighborhood of the sliding surface, the adaptive law is obtained through a Lyapunov function. The proposed motion and trajectory controller is then implemented on a USV prototype subject to parametric uncertainties and external perturbations. The experiments demonstrate the ability of the controller to constrain the sliding variable to the desired closed-loop dynamics and converge within the desired settling time. Highlights: Unmanned Surface Vehicles (USV) are impacted by uncertainties and disturbances USV need to perform finite-time tasks like complex maneuvers and obstacle avoidance Finite-time control is guaranteed with the proposed adaptive sliding mode controller The proposed controller efficiency is illustrated with experiments on a USV prototype